Capacity Building in Christian Religious Education, Family Education, and Entrepreneurial Spirit Development: Strengthening Services and Growth of Congregation at Toraja Church in Kuala Lumpur - Rantung, Djoys Anneke; SIANIPAR, DESI; Limbong, Mesta; Silvanita, Ktut; Widiarty, Wiwik Sri; Kaliey, Ingrid M (Universitas Kristen Cipta Wacana, 2025)
This community service program aims to strengthen the effectiveness of ministry and the growth of the diaspora congregation of the Toraja Church in Kuala Lumpur through capacity building in Christian Religious Education, Family Education, and Entrepreneurial Spirit Development. The program was conducted by five lecturers and one student from four study programs at Universitas Kristen Indonesia (UKI), in collaboration with the Toraja Church in Kuala Lumpur. Based on informal consultations, the congregation expressed a need for training in church ministry, family education, child protection, and entrepreneurial mindset development. The capacity-building activities were delivered through interactive seminars. These activities emphasized strengthening theological understanding of ministry and family, enhancing family communication skills, and introducing practical entrepreneurial principles relevant to the diaspora context. The outcomes of the training indicated increased knowledge, greater confidence in implementing church ministry and family education practices, and heightened motivation to initiate small-scale entrepreneurial efforts. This program demonstrates that an integrative capacity-building model is effective in supporting the holistic growth of diaspora congregations.